2020
DOI: 10.1021/acs.jmedchem.9b01526
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lethality in Pancreatic Cancer: Discovery of a New RAD51-BRCA2 Small Molecule Disruptor That Inhibits Homologous Recombination and Synergizes with Olaparib

Abstract: Synthetic lethality is an innovative framework for discovering novel anticancer drug candidates. One example is the use of PARP inhibitors (PARPi) in oncology patients with BRCA mutations. Here, we exploit a new paradigm based on the possibility of triggering synthetic lethality using only small organic molecules (dubbed “fully small-molecule-induced synthetic lethality”). We exploited this paradigm to target pancreatic cancer, one of the major unmet needs in oncology. We discovered a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 37 publications
1
64
0
Order By: Relevance
“…In a very recent report, Cavalli et al identified a new class of RAD51-BRCA2 gene disruptors having quinolinone-pyrazoline hybrid structures [73]. After extensive structure-activity relationship studies they concluded that compound 23 was able to bind to its target (RAD51) and to inhibit the protein-protein interaction between RAD51 and BRCA2.…”
Section: Other Benzene-fused Six Membered Heterocyclic Pyrazoline Hybmentioning
confidence: 99%
“…In a very recent report, Cavalli et al identified a new class of RAD51-BRCA2 gene disruptors having quinolinone-pyrazoline hybrid structures [73]. After extensive structure-activity relationship studies they concluded that compound 23 was able to bind to its target (RAD51) and to inhibit the protein-protein interaction between RAD51 and BRCA2.…”
Section: Other Benzene-fused Six Membered Heterocyclic Pyrazoline Hybmentioning
confidence: 99%
“…Inhibitors that suppress the D-loop activity of RAD51 have also been reported (Budke et al, 2019;Lv et al, 2016), although several optimized versions also exhibit DNA-intercalating activity (Budke et al, 2019). On the other hand, reports of small molecules and peptides have been published that claim to disrupt the interaction between RAD51 and the BRC repeats, or between RAD51 multimers (Bagnolini et al, 2020;Falchi et al, 2017;Nomme et al, 2010;Roberti et al, 2019;Trenner et al, 2018;Vydyam et al, 2019;Zhu et al, 2013Zhu et al, , 2015Ward et al, 2017). However, the lack of specific structural information concerning the interaction of these inhibitors with RAD51 has impeded the precise exploration of structure-activity relationships, and the efficient development of more potent compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Small organic molecules mimicking BRC4 and inhibiting RAD51-BRCA2 interaction have also been reported in the literature (Bagnolini et al , 2020; Falchi et al ., 2017; Roberti et al , 2019; Zhu et al , 2013). The molecular mechanism here reported can eventually shed further light on the complex HR pathway, which inhibition, through peptides or small molecules, could be rather key for the discovery of innovative anticancer compounds.…”
Section: Discussionmentioning
confidence: 89%